Fungicidal activity of human monocyte-derived multinucleated giant cells induced in vitro by Paracoccidioides brasiliensis antigen - Pereira do Nascimento, Magda Paula [UNESP]; Soares, Ângela Maria Victoriano de Campos [UNESP]; Dias-Melicio, Luciane Alarcao [UNESP]; Parise-Fortes, Maria Rita [UNESP]; Rodrigues Martins, Rosana Aparecida [UNESP]; Nakaira, Erika Takahashi [UNESP]; Serrao Peracoil, Maria Terezinha [UNESP] (Springer, 2008)
Multinucleated giant cells (MGC) are characteristic cells in granulomatous disorders such as paracoccidioidomycosis (PCM) and also are formed in vitro from peripheral blood mononuclear cells by several stimuli. In this study, the authors investigated in vitro formation of MGC derived from monocytes of healthy individuals, stimulated with Paracoccidioides brasiliensis antigen (PbAg), compared with other stimuli such as IFN-gamma and supernatant of Con-A-stimulated peripheral blood mononuclear cells (CM-ConA). Besides, the fungicidal activity of monocytes and monocyte-derived MGC challenged with P. brasiliensis were compared, at a ratio of one fungus per 50 monocytes. Results demonstrated that PbAg, IFN-gamma, and CM-ConA stimuli were able to induce MGC generation, with fusion indices significantly higher than control cultures. Striking results were observed when MGC induced by PbAg and IFN-gamma presented higher fungicidal activity than monocytes, submitted to the same stimuli, showing a better capacity of these cells to kill P. brasiliensis. In summary, the results suggest that PbAg is able to induce MGC generation, and these cells presented higher fungicidal activity against P. brasiliensis than monocytes.
Keywords: fungicidal activity; multinucleated giant cells; paracoccidioides brasiliensis; interferon-gamma